Possibilidades de desenvolvimento do ecoturismo na Área de Proteção Ambiental Morro do Urubu (Aracaju SE) - Pinto, Joyce Barreto (2008)
The tourism involves 52 sectors of the economy, generating thousands of jobs and make billions of dollars being circulated. However, it causes also several negative impacts, particularly with regard to natural and cultural aspects. Since the mid- 60, when the first initiatives against some factors related to the current model of development and to social and environmental problems caused by this, the reality is undergoing changes. Trailer to this fact, it emerged new segments of tourism linked to nature and concerned about the environmental issue, such as ecotourism. The relationship between environment and tourism is very intrinsic, especially when speaking in units of conservation. The National System of Conservation Units (SNUC) provides in some categories the indirect intervention of people, facilitating the relationship with the communities involved. The ecotourism, tourism segment that before the strengthening of environmental awareness and demand for improved quality of life, has gained more supporters in recent years, characterizing itself as an alternative to the development of the people around. It believes that the benefits should cover both the conservation of the areas visited as a socio-economic issue of the local community. In view of this reality, this work is proposed to analyse the natural and socio-cultural aspects in the Area of Environmental Protection Morro do Urubu and possibilities for the development of the ecotourism in this area. The Environmental Protection Area of Morro do Urubu is located in the area north of Aracaju and contains the unique vegetation cover with remnants of Atlantic Forest in the city. It is concluded that even in the nascent state, ecotourism, especially in APA Morro do Urubu has great potential to grow into ecoturístico product.